A new species of Oxelytrum Gistel (Coleoptera, Silphidae) from southern Argentina, with a key to the species of the genus - Oliva, Adriana (2012)
A new species of the forensically interesting genus Oxelytrum Gistel (Coleoptera, Silphidae), O. selknan, is described from Santa Cruz and Tierra del Fuego provinces, Argentina. The new species resembles O. biguttatum (Philippi) in outer aspect, but has different male genitalia, in particular a median lobe longer than the paramera. All the described species of Oxelytrum have the median lobe shorter than the paramera. The internal sac, as far as it could be reconstructed from dry-pinned specimens, also shows differences between the two species. A key to the species of Oxelytrum is given and illustrated.